2007
DOI: 10.1152/jn.01317.2006
|View full text |Cite
|
Sign up to set email alerts
|

Response Properties of Neighboring Neurons in the Auditory Midbrain for Pure-Tone Stimulation: A Tetrode Study

Abstract: Seshagiri CV, Delgutte B. Response properties of neighboring neurons in the auditory midbrain for pure-tone stimulation: a tetrode study. J Neurophysiol 98: 2058J Neurophysiol 98: -2073J Neurophysiol 98: , 2007. First published August 1, 2007; doi:10.1152/jn.01317.2006. The complex anatomical structure of the central nucleus of the inferior colliculus (ICC), the principal auditory nucleus in the midbrain, may provide the basis for functional organization of auditory information. To investigate this organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 52 publications
7
31
1
Order By: Relevance
“…9). This same pattern also held true for bipolar and acoustic stimulation and is consistent with previous studies of IC responses to acoustic tones (Rose et al 1963;Aitkin et al 1994;Harris et al 1997;Seshagiri and Delgutte 2007) and electrical pulse trains (Bierer et al 2010). Interestingly, in the present study, onset responses to acoustic and electrical stimuli could be quite broad, extending over several millimeters (or several octaves) of the IC tonotopic axis at higher levels, whereas sustained responses covered a much narrower extent (for acoustic stimuli at 60 dB SPL the extent was FIG.…”
Section: Discussionsupporting
confidence: 90%
“…9). This same pattern also held true for bipolar and acoustic stimulation and is consistent with previous studies of IC responses to acoustic tones (Rose et al 1963;Aitkin et al 1994;Harris et al 1997;Seshagiri and Delgutte 2007) and electrical pulse trains (Bierer et al 2010). Interestingly, in the present study, onset responses to acoustic and electrical stimuli could be quite broad, extending over several millimeters (or several octaves) of the IC tonotopic axis at higher levels, whereas sustained responses covered a much narrower extent (for acoustic stimuli at 60 dB SPL the extent was FIG.…”
Section: Discussionsupporting
confidence: 90%
“…After correcting for the 10 -15% excess by which the dipole model tends to overestimate source distance (Mechler and Victor 2011), and estimating separately for different contact separation (⌬s) on the Thomas tetrodes, the R 50 recording radius was Ϸ80 -85 m for the smaller and intermediate tetrodes (⌬s ϭ 29 m and ⌬s 38 m, respectively) and Ϸ95-100 m for the larger tetrode (⌬s ϭ 45 m). These ranges of tetrode sensitivity are generally consistent with the characteristic linear span (can be Ͼ200 m) over which polytrodes reportedly register signals from cortical single units (Blanche et al 2005;Drake et al 1988) but remain significantly larger than the Ϸ50-to 70-m recording radii reported for twisted wire tetrodes (Gray et al 1995;Henze et al 2000;Maldonado et al 1997;Seshagiri and Delgutte 2007). There are several reasons the estimates can differ; the most important ones are difference in source model type, probe size (contact separation), and neuron size.…”
Section: The Recording Radius and Volume Of Tetrodessupporting
confidence: 74%
“…We have found that the recording volume (radius Ϸ100 m) of a stationary tetrode was much larger than its most frequently quoted antecedents (Ϸ60 m) (Gray et al 1995;Henze et al 2000;Maldonado et al 1997;Seshagiri and Delgutte 2007), that within this volume the isolation sensitivity was approximately homogeneous and the isolated fraction of neurons small (Ϸ0.3%), and that the neurons could be localized with a precision that was much smaller (radius Ϸ50 m) than the entire recording volume. This improved precision for localizing a cell requires that it is recorded by the tetrode in more than one position.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Considering that frequency is coded along one dimension of the ICC, this raises the possibility that temporal features may be coded spatially along the isofrequency laminae. There are animal studies that have shown that various temporal features, such as periodicity and latencies, are coded systematically along these ICC laminae Schreiner & Langner, 1988) under certain stimulus conditions (Krishna & Semple, 2000;Seshagiri & Delgutte, 2007). Thus, it is possible that we may need to stimulate along the frequency axis of the ICC to transmit varying pitch percepts and across different regions within these isofrequency laminae to transmit sufficient temporal information.…”
Section: Temporal Codingmentioning
confidence: 99%